Cross-sectional investigation of pneumococcal vaccination patterns in HIV patients at a tertiary care hospital in Riyadh, Saudi Arabia - Reem Binsuwaidan; Enas Mosaffer Alghamdi; Ethar Abdullhameed Otaif; Maram Saud ALqutaym; Yahya Ali Mohzari; Ahmed Ali Alrashed; Rowdan Zeyan Alderaan; Ahmed Ajlan Alsheheri; Alaa Alhubaishi; Lina I Alnajjar (Journal of Infection and Public Health)
Background: People living with HIV (PLWH) are recognized as a high-risk population for opportunistic infections, including community-acquired pneumonia (CAP). Therefore, the United States Centers for Disease Control and Prevention (US-CDC) and Saudi Ministry of health (MOH) advocate for pneumococcal vaccination among all PLWH as a crucial preventive measure against pneumococcal infections. Hence, this study aims to investigate the prescribing patterns of pneumococcal vaccines for PLWH at a tertiary care hospital. As PCV15 and PCV20 were not available until 2022, this study focuses on the prescribing patterns of PCV13 and PPSV23. Methods: This cross-sectional study was conducted to assess the prescribing patterns of pneumococcal vaccines among PLWH attending the HIV clinic at a tertiary hospital in Riyadh, Saudi Arabia. Utilizing medical records from PLWH who visited the HIV clinic between January 1987 and December 2022, demographic data, clinical characteristics, antiretroviral therapy details, and pneumococcal vaccination records were collected. Statistical analyses were performed using the Statistical Package for Social Sciences (SPSS) version 21 (SPSS Inc., Armonk, New York, USA). Results: Of the 346 identified patients, the majority (81 %) were male, with a median age of 45 years. A significant proportion had not received any pneumococcal vaccinations (98.6 %), while only 2 patients (0.56 %) completed the full series of pneumococcal vaccines (PCV13-PPSV23), and 3 patients (0.84 %) received a single dose of PCV13. Nearly all patients (99 %) reported regular attendance at the HIV clinic, with the vast majority (98.3 %) receiving antiretroviral therapy (ART). Conclusion: This study revealed a notable deficiency in pneumococcal vaccine coverage among PLWH. Therefore, additional measures are imperative to improve pneumococcal vaccine uptake and reduce the risk of invasive pneumococcal diseases within this vulnerable population.